Design, fabrication and testing of a multi - fruit grader - ABHILASH G. NAMBUDIRI GEETHA LEKSHMI LAKSHMI G; Dr. Sudheer K. P (Guide) (Tavanur 2001 Kelappaji College of Agricultural Engineering and Technology)
Design, fabrication and testing of a multi - fruit grader
Design, fabrication and testing of a multi - fruit grader